Analisis Pengaruh Penggunaan Dompet Digital Terhadap Perilaku Konsumtif Mahasiswa Universitas Palangka Raya Angkatan 2023 - Puput Iswandyah Raysharie; Argy' Dimaz Dzaky Bryllian; Anisa Rahmawati; Febrina Gracia Hawini; Juraida Titin Marliana; Lourensia Disa Natalia; Ragil Yudistira (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
In the era of the industrial revolution 5.0, extraordinary developments enslave the use of technology in the field of technology which also has an impact on other sectors, as in this study the use of technology in the economic sector which aims to determine whether Consumptive Behavior is influenced by Digital Wallets. This research was conducted at Palangkaraya University, Indonesia with a quantitative approach to the research population of 4,143 people, using sampling techniques by distributing G-forms through whats-App social media obtained 365 respondents from various faculties at Palangkaraya University the results were processed using the slovin formula and tested through Multiple Linear Regression Analysis, namely t test analysis where digital wallets (X) have a t-statistic of 9.0366 where the prob. (Significance) value is 0.000000, regression equation analysis, Simultaneous F test analysis with an f-statistic value of 81.660 with a prob. (F-statistic) value of 0.00000 (<0.05) and test analysis of the coefficient of determination with an Adjust R-Squared value of 0.181 so that the results show that digital wallets (X) have a significant effect on consumptive behavior (Y).